2018
DOI: 10.1038/s41598-018-23572-3
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Pelleted Hazel (Corylus avellana) Leaves Decreases Methane and Urinary Nitrogen Emissions by Sheep at Unchanged Forage Intake

Abstract: This study is the first to quantify the effects of hazel (Corylus avellana) leaves on methane and urinary nitrogen emissions, digestibility, nitrogen and the energy balance of ruminants. Four experimental pellets were produced with 0, 30% and 60% hazel leaves, the latter also with 4% polyethylene glycol. Hazel leaves gradually replaced lucerne. The diet was composed of the pellets and grass hay (80%: 20%). Six adult sheep were allocated to all four treatments in a 6 × 4 crossover design. Including hazel leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
0
13
0
2
Order By: Relevance
“…In a feeding experiment with sheep, Wang et al . (2018) demonstrated that C. avellana leaves also have a clear methane-mitigating effect in vivo . As a sole substrate, L. corniculatus has been reported to reduce CH 4 emissions in vivo (Pinares-Patiño et al ., 2003; Woodward et al ., 2004) and in vitro (Williams et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a feeding experiment with sheep, Wang et al . (2018) demonstrated that C. avellana leaves also have a clear methane-mitigating effect in vivo . As a sole substrate, L. corniculatus has been reported to reduce CH 4 emissions in vivo (Pinares-Patiño et al ., 2003; Woodward et al ., 2004) and in vitro (Williams et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Urine samples need to be collected with minimal contamination by feces. In sheep, samples of feces and urine can be collected in metabolic crates independent of the sex (e.g., Wang et al, 2018). In cattle, sampling of total urine varies depending on the sex of the experi-mental animal.…”
Section: Whole-animal Nitrogen Balance Studiesmentioning
confidence: 99%
“…Similarly, in a study conducted on adult sheep, hazel (Corylus avellana) leaves when supplemented at 50% of the total diet were able to reduce CH 4 emissions by 35% (per unit OM intake) compared to the control (ryegrass hay and lucerne pellets). Concomitantly, a substantial decrease in urinary N proportion of total N intake was observed without any negative effects on forage intake, apparent palatability, or body weight of the sheep [111]. However, despite the promising findings indicated by these studies, the antimethanogenic potential of the forages is not clearly linked to the tannin concentration, as evidenced by the high variability in results from different studies (Table 1).…”
Section: Current Findings On the Antimethanogenic Potential Of Trfsmentioning
confidence: 92%